Interleukin‐37 and Dendritic Cells Treated With Interleukin‐37 Plus Troponin I Ameliorate Cardiac Remodeling After Myocardial Infarction. Issue 12 (December 2016) - Zhu, Ruirui; Sun, Haitao; Yu, Kunwu; Zhong, Yucheng; Shi, Huairui; Wei, Yuzhen; Su, Xin; Xu, Wenbin; Luo, Quan; Zhang, Fangyuan; Zhu, Zhengfeng; Meng, Kai; et al.
Abstract : Background: Excessive immune‐mediated inflammatory reactions play a deleterious role in postinfarction ventricular remodeling. Interleukin‐37 (IL‐37) emerges as an inhibitor of both innate and adaptive immunity. However, the exact role of IL‐37 and IL‐37 plus troponin I (TnI)–treated dendritic cells (DCs) in ventricular remodeling after myocardial infarction (MI) remains elusive. Methods and Results: MI was induced by permanent ligation of the left anterior descending artery. Our results showed that treatment with recombinant human IL‐37 significantly ameliorated ventricular remodeling after MI, as demonstrated by decreased infarct size, better cardiac function, lower mortality, restricted inflammatory responses, decreased myocardial fibrosis, and inhibited cardiomyocyte apoptosis. In vitro, we examined the phenotype of IL‐37 plus TnI–conditioned DCs of male C57BL/6 mice and their capacity to influence the number of regulatory T cells. Our results revealed that IL‐37 plus TnI–conditioned DCs obtained the characteristics of tolerogenic DCs (tDCs) and expanded the number of regulatory T cells when co‐cultured with splenic CD4 + T cells. Interestingly, we also found that adoptive transfer of these antigen‐loaded tDCs markedly increased the number of regulatory T cells in the spleen, attenuated the infiltration of inflammatory cells in the infarct hearts, decreased myocardial fibrosis, and improved cardiac function. Conclusions: Our results reveal a beneficial role of IL‐37 or tDCs treated with IL‐37 plus TnI in post‐MI remodeling that is possibly mediated by reestablishing a tolerogenic immune response, indicating that IL‐37 or adoptive transfer of IL‐37 plus TnI–treated tDCs may be a novel therapeutic strategy for ventricular remodeling after MI.